1999
DOI: 10.1097/00005344-199905000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of the Spanish Trial on Treatment and Survival of Patients with Predominantly Mild Heart Failure

Abstract: A randomized open-label clinical trial was conducted to determine whether mortality, readmission, or quality of life differed between heart failure patients managed with captopril plus diuretics and those with digoxin plus diuretics. A total of 345 heart failure patients in New York Heart Association functional classes 2 and 3 without atrial fibrillation, dyspnea of bronchopulmonary origin, or hypertension not controlled with diuretics was randomized for digoxin (n = 175) or captopril (n = 170) treatment and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…A total of 47,662 subjects were included with a mean/median follow-up ranged from 12 weeks to 4.5 years. Of all 38 studies, six ( n = 8404) trials compared ARBs with placebo [ 13 , 43 47 ], while 32 trials ( n = 39,254) compared ACEIs with various control therapies (13 arms ( n = 10,134) compared ACEIs [ 2 – 6 , 23 30 ] with placebo treatment; 10 arms ( n = 8714) in which the comparator was active treatment [ 7 , 8 , 31 38 ]; and 9 arms ( n = 20,406) compared ACEIs with ARBs [ 9 12 , 14 , 39 42 ]). Two independent investigators (Y. X. and D.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 47,662 subjects were included with a mean/median follow-up ranged from 12 weeks to 4.5 years. Of all 38 studies, six ( n = 8404) trials compared ARBs with placebo [ 13 , 43 47 ], while 32 trials ( n = 39,254) compared ACEIs with various control therapies (13 arms ( n = 10,134) compared ACEIs [ 2 – 6 , 23 30 ] with placebo treatment; 10 arms ( n = 8714) in which the comparator was active treatment [ 7 , 8 , 31 38 ]; and 9 arms ( n = 20,406) compared ACEIs with ARBs [ 9 12 , 14 , 39 42 ]). Two independent investigators (Y. X. and D.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies that remained candidates for inclusion after the first examination were extensively analyzed. Of these studies, 1 was excluded because the follow‐up period was less than 12 weeks, 12 5 due to the absence of the enough data on atrial fibrillation, 13‐18 1 because it was a report of total data subsequently reported, 19 2 because they were subanalysis of studies included in the present analysis, 20,21 1 due to the lack of a control group, 22 and 1 because the primary outcome was hospitalization for atrial fibrillation and not the development of new‐onset or recurrence of atrial fibrillation (Table I) 23 . There were then seven trials used in this meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…However, at baseline, patients unable to withdraw from digitalis were excluded from the study 52 . A two‐year mortality study also showed a 20.9% versus 31.9% (log rank test p=0.07) for captopril and digoxin respectively, with no other statistically significant differences in clinical and adverse events 53 . Thus, digitalis in CHF management is on a par with ACE inhibitors.…”
Section: Digitalis In Chronic Chf With Sinus Rhythmmentioning
confidence: 93%
“…52 A two-year.mortality study also showed a 20.9% versus 31.9% (log rank test p=0.07) for captopril and digoxin respectively, with no other statistically significant differences in clinical and adverse events. 53 Thus, digitalis in CHF management is on a par with ACE inhibitors. Other inotropic agents such as dobutamine, beta-agonists, milrinone and enoximone have shown excess mortality.…”
Section: Digitalis In Chronic Chf With Sinus Rhythmmentioning
confidence: 99%